Time-Limited Waqf in Indonesian and Yemeni Law: A Comparative Study Based on National Legislation and Fiqh Approaches - Al-Baiti, Mohsen Farid Abdulrahman; Khoirudin, Ahmad (UIN Siber Syekh Nurjati Cirebon, 2025)
This study compares the regulation of time-limited waqf berjangka in Indonesia and Yemen, focusing on Indonesia's Law No. 41 of 2004 on Waqf and Yemen's Qānūn al-Waqf al-Sharʿī of 1992. The primary objective of this study is to analyze the validity of temporary endowments (mu'aqqat) within both legal systems and how national regulations affect the acceptance of time-limited endowments. In Indonesia, time-limited endowments are explicitly accommodated in the law, allowing for more flexible management of endowments. In contrast, Yemen's regulations prioritize the permanent (taʾbīd) nature of waqf, limiting the possibility of time-limited endowments. This study employs a cross-mazhab fiqh approach, comparing the views of the Maliki school, which permits temporary endowments, with the Shafi'i and Hanbali schools, which tend to reject them. The findings of this study reveal a shift in the legal paradigm of waqf, from traditional practices to a more modern model, influenced by the social, political, and economic dynamics in each country. The novelty of this research lies in the direct comparison of two different legal systems, offering a new perspective on the acceptance and application of time-limited waqf in the context of socio-economic development. These findings contribute to a deeper understanding of the role of waqf in contemporary legal dynamics.Keywords: time-limited waqf; waqf law; Indonesia; Yemen; Fiqh; Comparative Law